(3GdbGfhf GdOhdj GdEfSGfj GdebGQf Hjf GdfXQjGJ GdJchjfjI hGdGJLGgGJ GdJaSjQjI (B/s - (3CHh YjWI, GdSjO,s 1965- ((3GdbGgQI (B: s (3OGQ GdfgVI GdYQHjI ddfTQ hGdJhRjY ; s (3OHj, GdEeGQGJ GdYQHjI GdeJMOI (B:s (3OGQ GdfgVI GdYdejI, s, 2018)
(3jJfGhd cJGH (B((3GdbGfhf GdOhdj GdEfSGfj GdebGQf Hjf GdfXQjGJ GdJchjfjI hGdGJLGgGJ GdJaSjQjI(B) (3GdPj bGe HJCdjag O(B. (3GdSjO CHh YjWI aj MhGdj (B(167) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdbGfhf GdOhdj GdEfSGfj GdebGQf(B)(3, eSJYQVG GdehVhYGJ GdJGdjI (B: (3JUOjQ GdcJGH hGdeMJhi, GdHGH GdChd (B: (3GdJYQja HGdbGfhf GdOhdj GdEfSGfj GdebGQf, GdHGH GdKGfj (B: (3BKGQ GdfRGYGJ GdOhdjI GdeSdMI aj GdbGfhf GdOhdj GdEfSGfj GdebGQf(B. s
(3HHdjhLQGajI (B: (3UaMI (B150-164.s
Keywords: (3GdbGfhf GdEfSGfjs; (3GdbGfhf GdOhdjs; (3Mbhb GdEfSGf (B((3bGfhf Ohdj(B)s; (3GdESdGe hGdbGfhf GdEfSGfjs; (3GdMQH (B((3bGfhf Ohdj(B)s; (3GdefXeGJ GdOhdjIs; (3CSQi GdMQH s; (3GdfRGY GdOhdj GdeSdMs; (3GdbGfhf GdOhdj GdESdGej GdEfSGfjs; (3GdMQHs